A synergetic stabilization and strengthening strategy for two-dimensional ordered hybrid transition metal carbides. Issue 47 (26th November 2018) - Fu, Zhongheng; Zhang, Shihao; Legut, Dominik; Germann, Timothy C.; Si, Chen; Du, Shiyu; Francisco, Joseph S.; Zhang, Ruifeng
Abstract : A strengthening strategy by means of constitutional hybridization. Abstract : Two-dimensional (2D) transition metal carbides (MXenes) exhibit excellent thermodynamic stability and remarkable mechanical strength and flexibility, as well as rich functionality, which attract considerable interest due to their potential application for high-performance flexible and stretchable devices. However, premature phonon instability of some non-hybrid MXenes was recently found to intrinsically limit their strength and flexibility, evoking passionate curiosity in pursuing an effective solution for more impressive mechanical properties. In this work, on the basis of an alloying strengthening mechanism, a combinational strategy is proposed to build ordered hybrid M2 ′′M′C2 O2 (M′′ = Mo, W; M′ = Ti, Zr, Hf) with remarkable dynamic stability and superior mechanical properties by hindering the premature phonon instability originating from the outer transition metals. By means of comprehensive screening, symmetrical-Mo2 TiC2 O2 is interestingly found to possess excellent stability at equilibrium and outstanding tolerance to phonon instability during straining compared to its Ti counterpart, being attributed to the character of the robust Mo-d z 2 and O-p z hybridization. Although similar optical phonon soft modes appear in Ti3 C2 O2 and Mo2 TiC2 O2 under multiple loadings, the latter is much stiffer during straining. An in-depth analysis of deformed electronic structures reveals that a strain-induced increasing density of states in the vicinity of the Fermi level mainly composed of Mo-d z 2 states facilitates the fatal phonon softening in Mo2 TiC2 O2 under biaxial tension, while differing from the mechanical instability in Ti3 C2 O2 triggered by a Peierls transition. Our findings provide a novel stabilization and strengthening strategy for 2D materials, and pave a new way for searching for 2D material candidates in designing flexible devices.